Basisopleidingsprogramma voor hulpverleners van seksueel misbruikers - De Doncker, Christel; Vankerckhoven, Christel; Cosyns, Paul (Pedofilie)
"Fonds Suzan Daniel (FSD)Themanummer Antenne : 16 (1998) 2 Christel De Doncker; Christel Vankerckhoven; Paul Cosyns"